Pengaruh Motivasi terhadap Produktivitas Kerja Karyawan pada Lembaga Pelatihan Kerja Wajo Intelektual Mandiri Kabupaten Wajo - Ardiyanti Ardiyanti; Yuniarni Yusuf; Andi Patotori Arismunandar (Studi Administrasi Publik dan ilmu Komunikasi, 2025)
In this study, a quantitative research approach was used, with two variables: motivation as the independent variable and work productivity as the dependent variable. The survey method was employed, with a sample of 26 employees from the Wajo Intellectual Mandiri Job Training Institute. The data analysis techniques used included quantitative descriptive analysis, correlation analysis, and simple regression analysis. Data collection was carried out through observation, questionnaires, and documentation. The findings indicate that both the motivation and work productivity variables are rated highly, based on the respondents' answers from the questionnaire distribution. The results demonstrate a positive relationship between motivation and employee work productivity at the Wajo Intellectual Mandiri Job Training Institute in Wajo Regency. This study highlights the importance of motivation in enhancing work productivity and provides valuable insights for improving organizational performance by fostering motivation among employees. The findings can be used as a basis for developing strategies to optimize employee productivity in similar organizational settings.